Why we whisper : restoring our right to say it's wrong - DeMint, Jim (Rowman & Littlefield Publishers, 2008)
Why Whisper? calls on Americans who believe in traditional values to resist the urge to stay silent and thus safe under the shameless onslaught of pressure, intimidation, and ridicule from the San Francisco-loving, NY Times reading, multicultural, anti-business, French-first, tree-hugging secular progressives and liberal political elites.